2013
DOI: 10.2215/cjn.01880213
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Cardiovascular Mortality after Kidney Transplantation

Abstract: Background and objectives Circulating fibroblast growth factor 23 (FGF23) is associated with adverse cardiovascular outcomes in CKD. Whether FGF23 predicts cardiovascular mortality after kidney transplantation, independent of measures of mineral metabolism and cardiovascular risk factors, is unknown.Design, setting, participants, & measurements The association between plasma C-terminal FGF23 and cardiovascular mortality was analyzed in a single-center prospective cohort of 593 stable kidney transplant recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 37 publications
5
93
1
1
Order By: Relevance
“…Most studies show a near-linear increase in risk with increasing FGF23 concentrations, with available (but limited) data suggesting comparable results between cFGF23 and iFGF23 (42,45). With respect to renal outcomes, higher FGF23 concentrations have been associated with earlier initiation of chronic dialysis and significant decrements in renal function in patients with nondialysis-dependent CKD (4,5,36,46), again yielding improvements in event reclassification (19%) (47), and have variably predicted graft failure after kidney transplantation (44,45). Moreover, FGF23 predicts progression in disease-specific causes of renal failure, including IgA nephropathy, and those patients with heavy proteinuric diabetic kidney disease (48,49).…”
Section: Fgf23 and Adverse Outcomes In Ckdmentioning
confidence: 98%
See 1 more Smart Citation
“…Most studies show a near-linear increase in risk with increasing FGF23 concentrations, with available (but limited) data suggesting comparable results between cFGF23 and iFGF23 (42,45). With respect to renal outcomes, higher FGF23 concentrations have been associated with earlier initiation of chronic dialysis and significant decrements in renal function in patients with nondialysis-dependent CKD (4,5,36,46), again yielding improvements in event reclassification (19%) (47), and have variably predicted graft failure after kidney transplantation (44,45). Moreover, FGF23 predicts progression in disease-specific causes of renal failure, including IgA nephropathy, and those patients with heavy proteinuric diabetic kidney disease (48,49).…”
Section: Fgf23 and Adverse Outcomes In Ckdmentioning
confidence: 98%
“…Multiple prospective studies have shown a consistent link between higher FGF23 concentrations and increased risk of both death and cardiovascular events across the entire spectrum of renal disease (4,5,(42)(43)(44)(45). Most studies show a near-linear increase in risk with increasing FGF23 concentrations, with available (but limited) data suggesting comparable results between cFGF23 and iFGF23 (42,45).…”
Section: Fgf23 and Adverse Outcomes In Ckdmentioning
confidence: 99%
“…Finally, we performed mediation analyses to identify potential causal pathways shared among T 50 and two established nontraditional cardiovascular risk factors in RTR: N-terminal-pro brain natriuretic peptide (NT-proBNP) 12 and fibroblast growth factor 23 (FGF23). 13 …”
mentioning
confidence: 99%
“…Although patients with the highest FGF23 levels were characterized by an overall high cardiovascular risk profile, the associations between FGF23 and mortality (cardiovascular and all-cause) remained significant after adjustment for several major cardiovascular risk factors, including Framingham risk factors, suggesting that FGF23 is a strong and independent risk marker. 16 In addition, Dominguez and associates reported associations between FGF23 and mortality, with events related to cardiovascular disease more likely in individuals with lower fractional excretion of phosphate independent of PTH and kidney function. In such individuals, the renal tubular response to FGF23 may be suboptimal.…”
Section: Structure and Function Of Fibroblast Growth Factor 23mentioning
confidence: 99%